2022
DOI: 10.3389/fpsyg.2021.728390
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Psychosocial Risk Factors and Improving Employee Well-Being in Emergency Departments: A Realist Evaluation

Abstract: This study reports the findings of a 2.5 year intervention project to reduce psychosocial risks and increase employee well-being in 15 emergency departments in the Netherlands. The project uses the psychosocial risk management approach “PRIMA” which includes cycles of risk assessment, designing and implementing changes, evaluating changes and adapting the approach if necessary. In addition, principles of participative action research were used to empower the departments in designing and implementing their own … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Other notable interventions which reported positive findings included: a video debriefing programme to support well-being 70 ; tactile massage and hypnosis 71 ; and Pups Assisting Wellness for Staff. In contrast, de Wijn and van der Doef 44 found less positive findings in their PRIMA intervention (psychosocial risk management approach) which decreased levels of work engagement and showed no change in burnout levels. Despite this, they also reported that in EDs where employees were more involved in the process, more positive changes in job factors and well-being were seen.…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…Other notable interventions which reported positive findings included: a video debriefing programme to support well-being 70 ; tactile massage and hypnosis 71 ; and Pups Assisting Wellness for Staff. In contrast, de Wijn and van der Doef 44 found less positive findings in their PRIMA intervention (psychosocial risk management approach) which decreased levels of work engagement and showed no change in burnout levels. Despite this, they also reported that in EDs where employees were more involved in the process, more positive changes in job factors and well-being were seen.…”
Section: Methodsmentioning
confidence: 89%
“…The job demands-control model 41 was used as a framework for a quantitative survey study 42 while the job demands-resources model 43 was used in both of de Wijn et al ’s quantitative studies. 44 45 Both models were developed within the field of occupational psychology.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study aimed to identify the prevalence of psychosocial risks in health providers, as well as to identify if some of the sociodemographic factors are linked to them. To this end, and considering that workers constantly face intense work pressure, it is essential to effectively address the experiences and situations to which they are exposed, even more so knowing that these can have a significant impact on their emotions, giving rise to psychosocial risks that they affect both their personal wellbeing and their performance at work, with organizations being the main protagonists that generate psychosocial risks (De Wijn & Van, 2022;Wu et al, 2022); this is how this study becomes relevant, since making a diagnosis regarding the prevalence of psychosocial risks is a concern in all organizations; in this regard, Talavera-Velasco et al (2018) establishes that the constant concern of leaders to obtain high quality standards is causing overwhelming working conditions that, independently of affecting the attitude of the worker, they face adverse situations at work that affect their well-being, which has a negative impact their job performance (Di Tecco et al, 2020;Madrid et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, NHCW staff of hospitals can also be at risk [11,12], with working environment described as the main risk factor [13]. Indeed, the medical staff, especially those working in emergency departments are exposed to psychosocial risk factors because of the type of work they do [58,59]. Moreover, the COVID-19 pandemic has worsened the situation all around the world [60][61][62].…”
Section: Discussionmentioning
confidence: 99%